2003
DOI: 10.1039/b301723k
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in physico-chemical characteristics of River Yamuna in Haryana and its ecological best-designated use

Abstract: Various physico-chemical characteristics of the River Yamuna flowing in Haryana through Delhi were studied in the summer (April 1998) and winter (Jan.-Feb. 1999). Ecological parameters like dissolved oxygen (DO), pH, nitrate (NO3-), sulfate (SO4(2-)), and phosphate (PO4(3-)), were analyzed and compared with standard permissible limits to assess the best-designated use of the river water for various purposes. The river in Delhi upstream was of better quality whereas the Delhi downstream stretch was polluted as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(80 citation statements)
references
References 4 publications
7
71
0
2
Order By: Relevance
“…This elevation of sodium concentration at Kalleeb Ebiar village during summer might be due to the high mobility of sodium ion and dominates in the natural solutions in the form of effluents near sampling site. The obtained results are in agreement with Ravindra et al (2003) and Ezzat et al (2012). Meanwhile, they are in contrast with Chandra et al (2006) and Hassanein et al (2013) who found the highest concentration of sodium during winter.…”
Section: Sodiumsupporting
confidence: 83%
“…This elevation of sodium concentration at Kalleeb Ebiar village during summer might be due to the high mobility of sodium ion and dominates in the natural solutions in the form of effluents near sampling site. The obtained results are in agreement with Ravindra et al (2003) and Ezzat et al (2012). Meanwhile, they are in contrast with Chandra et al (2006) and Hassanein et al (2013) who found the highest concentration of sodium during winter.…”
Section: Sodiumsupporting
confidence: 83%
“…Em 50% das amostragens realizadas, valores de OD estiveram abaixo de 5,0 mg L -1 para os dois locais monitorados o que, segundo alguns autores, pode ser atribuído à presença de matéria orgânica biodegradável e à utilização de OD por micro e macro fauna, resultando no consumo de OD e, portanto, em concentrações menores. 24,25 Os corpos aquáticos monitorados apresentaram condições que possibilitam a presença de vida aquática, porém houve casos em que a concentração de oxigênio dissolvido foi elevada, como é o caso do CAPRP (concentração de OD de 11,1 mg L -1 para Julho/07, por exemplo), que recebe efluentes domésticos clandestinamente a montante do local de coleta e, jusante do PRP. Concentrações de OD acima da saturação podem ser indicativas de início de processo de eutrofização, fenômeno no qual o processo de fotossíntese realizado pelas algas contribui para a elevação das concentrações de OD na água, bem como a ocorrência de temperaturas da água ao redor de 21 o C no período do inverno.…”
Section: Perfil Temporal Mensalunclassified
“…Thus the single parameter of TDS can give a reasonable good indication of a number of parameters [14].…”
Section: Discussionmentioning
confidence: 99%